Static and dynamic photoluminescence and photocatalytic properties of uniform, monodispersed up/down-converting, highly luminescent, lanthanide-ion-doped beta-NaYF4 phosphor microcrystals with controlled multiform morphologies - Padhye, Preeti; Poddar, Pankaj (Journal of Materials Chemistry A, 2014)
Lanthanide-ion-doped, single-crystalline hexagonal phase NaYF4 microcrystals with multiform morphologies, such as microrods, hexagonal microprisms, and spindle-like structures, were fabricated via a cationic/anionic binary capping agent system: CTAB and a tri-sodium citrate-assisted hydrothermal route. The influence of synthesis conditions on the crystalline morphology was studied and the possible growth mechanisms are presented systematically. The down-conversion and up-conversion photoluminescence (PL) properties of beta-NaYF4:Ln(3+) (Ln = Tb, Yb/Er, and Yb/Tm) were investigated. The static and dynamic PL studies of beta-NaYF4:5% Tb3+ showed strong dependence of luminescent properties on the crystalline morphology. Furthermore, the beta-NaYF4:5% Tb3+ phosphors exhibited efficient photocatalytic activity under UV as well as solar light irradiation, and showed enhanced selectivity towards methylene blue. Moreover, the morphological effect on the photocatalytic activity of beta-NaYF4:5% Tb3+ crystals has also been studied. The high luminescence efficiency and strong photocatalytic activity of beta-NaYF4:5% Tb3+ make them a potential phosphor material and promise to provide a gateway into other applications as in biology and materials sciences.